Faktor Risiko Penyalahgunaan Narkoba pada Remaja - Sheira Indah Anjani; High Boy Karmulrubog Hutasoit (Medula, 2022)
Adolescence is a time of physical, psychological, and social and emotional changes. At this stage of life, adolescents adopt behaviors that can lead to various health risks, including drug use. For adolescents, substance use tends to be acquired through experimentation and curiosity, especially through peers. Risk factors that potentially predispose adolescents to substance use include experimentation, lack of awareness, poor parental monitoring, peer influence, family and psychological problems. Risk factors can influence drug abuse in several ways. The more risk a child is exposed to, the more likely the child will abuse drugs. Some risk factors are very strong, but may not affect drug abuse unless certain conditions apply. Having a family history of substance abuse, for example, puts a child at risk for drug abuse. However, in an environment without drug-abusing peers and strong anti-drug norms, the child is less likely to abuse drugs and the presence of multiple protective factors can reduce the impact of some risk factors. For example, strong protections such as parental support and involvement can reduce the influence of strong risks, such as having peers who abuse substances. Adolescents have poor knowledge, attitudes and perceptions about pre-intervention of drug abuse. Interventions including health and psycho-education had effective results on knowledge, attitudes, and perceptions of adolescents about substance abuse. In dealing with drug prevention in adolescents, much special attention needs to be paid to individual factors because most of the findings are discussed in relation to these factors. With the increasing trend of drug abuse, it will be very important to focus research specifically on this area. This literature review discusses risk factors and prevention of drug abuse in adolescents